The Impact of Firm Performance on Annual Report Readability - Gu, Shuibin; Dodoo, Regina Naa Amua (International Research Journal of Business Studies, 2021)
This paper attempts to find the impact of firm performance on annual report readability. This study consists of 15 listed firms on the Ghana Stock Exchange within the period 2008 to 2017. The study applies Gunning Fog Index to measure annual report readability and measures Firm Performance using Return on Assets (ROA) by applying the fixed and random effect method. Per the Hausman test, the random effect method was accepted; the result stated that firm performance positively relates to annual report readability. In addition, the study finds out that corporate governance exerted a negative influence on the readability of the annual report. Finally, the study adopts F-MOLS to test Robustness. Regulators can consider improving and writing plain disclosure laws to improve annual report readability.